The impact of self-stigma on college students' attitudes toward professional psychological help-seeking: serial-mediated effects of discrimination perceptions and core self-evaluations - Chen, Daoliang; Wu, Yiling; Qian, Ling; Zhou, Ying (Frontiers in Psychology, 2025)
PurposeTo explore the role of self-stigma as predictor of college students' attitudes toward professional psychological help-seeking, as well as the separate and serial mediating roles of discrimination perceptions and core self-evaluations between the two.MethodsA survey of 574 college students was conducted using the Psychological Help-Seeking Stigma Scale, the Perception of Discrimination Scale, the Core Self-Esteem Scale, and the Attitudes toward Professional Psychological Help-Seeking Scale; descriptive statistics and correlation analyses were conducted using SPSS 25.0; and mediation model tests were conducted using Mplus 8.0.ResultsSelf-stigma negatively predicted college students' attitudes toward professional psychological help-seeking (β = −0.13, p < 0.01), and discrimination perceptions and core self-evaluations had a significant serial mediation between self-stigma and attitudes toward professional psychological help-seeking, with 95% confidence intervals of [−0.06, −0.01] and mediation effect sizes of −0.04.ConclusionSelf-stigma can not only directly predict college students' attitudes toward professional psychological help-seeking, but also indirectly predict college students' attitudes toward professional psychological help-seeking through the serial -mediated effects of discrimination perceptions and core self-evaluations.